Exploring Inbound International Students’ Choice Architecture through University Webpages - Craig, Chris D.; Stokes, Joe; Drea, Catherine (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2026)
Shifting funding models have made Ontario universities increasingly reliant on international students for economic viability. However, recent federal study permit caps have intensified an already competitive recruitment landscape. This study aimed to identify the key factors—or determinants—that inform international students’ university applications and to assess how effectively Ontario universities communicate this information on their websites. Furthermore, we sought competitive intelligence into whether universities communicated the determinants effectively through international studies webpages. The research followed a four-phase systematic inquiry to gather actionable insight through environmental scanning, grouping, competition analysis, and findings. Environmental scanning involved gathering industry trends and implications, forecasting potential issues, outlining a focal point, and establishing a database. The database informed the grouping phase, resulting in the selection of 12 university international studies websites for further review. Additionally, we derived 15 determinants and four emergent themes—geography, employment & finance, institutional information, and student perspectives—from a systematic report review outlining perceptions from over 171,000 students and 1,399 international degree-granting institutions. Competition analysis involved scanning and evaluating selected university webpages for effectiveness and the determinants. The findings indicate diverse approaches and varying abilities to communicate determinants. Also, higher-ranked universities transmit information more effectively. Study limitations include focusing on two English-language provinces and using secondary aggregated data to source determinants. The study addresses two research gaps: First, we foster awareness of higher education organizational practices, and second, we detail a Canadian perspective on inbound university student mobility.